Riboregulators in plant development. (23rd November 2007) - Laporte, P.; Merchan, F.; Amor, B.B.; Wirth, S.; Crespi, M.
Abstract : npcRNA (non-protein-coding RNAs) are an emerging class of regulators, so-called riboregulators, and include a large diversity of small RNAs [miRNAs (microRNAs)/siRNAs (small interfering RNAs)] that are involved in various developmental processes in plants and animals. In addition, several other npcRNAs encompassing various transcript sizes (up to several kilobases) have been identified using different genomic approaches. Much less is known about the mechanism of action of these other classes of riboregulators also present in the cell. The organogenesis of nitrogen-fixing nodules in legume plants is initiated in specific root cortical cells that express the npcRNA MtENOD40 ( Medicago truncatula early nodulin 40). We have identified a novel RBP (RNA-binding protein), MtRBP1 ( M. truncatula RBP 1), which interacts with the MtENOD40 RNA, and is exported into the cytoplasm during legume nodule development in the region expressing MtENOD40 . A direct involvement of the MtENOD40 RNA in the relocalization of this RBP into cytoplasmic granules could be demonstrated, revealing a new RNA function in the cell. To extend these results, we searched for npcRNAs in the model plant Arabidopsis thaliana whose genome is completely known. We have identified 86 novel npcRNAs from which 27 corresponded to antisense RNAs of known coding regions. Using a dedicated 'macroarray' containing these npcRNAs and a collection of RBPs, we characterized their regulation in different tissues and plants subjected to environmental stresses. Most of the npcRNAs showed high variations in gene expression in contrast with the RBP genes. Recent large-scale analysis of the sRNA component of the transcriptome revealed an enormous diversity of siRNAs/miRNAs in the Arabidopsis genome. Bioinformatic analysis revealed that 34 large npcRNAs are precursors of siRNAs/miRNAs. npcRNAs, which are a sensitive component of the transcriptome, may reveal novel riboregulatory mechanisms involved in post-transcriptional control of differentiation or environmental responses.